2009
DOI: 10.1145/1539024.1508959
|View full text |Cite
|
Sign up to set email alerts
|

Thinking about computational thinking

Abstract: Jeannette Wing's call for teaching Computational Thinking (CT) as a formative skill on par with reading, writing, and arithmetic places computer science in the category of basic knowledge. Just as proficiency in basic language arts helps us to effectively communicate and in basic math helps us to successfully quantitate, proficiency in computational thinking helps us to systematically and efficiently process information and tasks. But while teaching everyone to think computationally is a noble goal, there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(98 citation statements)
references
References 8 publications
3
87
0
8
Order By: Relevance
“…(Barr, Harrison & Conery, 2011;Basawapatna et al, 2011;Berland & Wilensky, 2015;Bers, 2010;ISTE & CSTA, 2011;Denning, 2012;Furber, 2012;Guzdial, 2008;Kafai, 2016;Kilpeläinen, 2010;Lu & Fletscher, 2009;NAACE, 2014;Papert, 1996;Snapp & Neumann, 2015;Williamson, 2015;Williamson, 2016) ies. Basawapatna et al, 2011;Berland & Wilensky, 2015;Bers, 2010;ISTE & CSTA, 2011;Furber, 2012;Grover & Pea, 2013;Guzdial, 2008;Kilpeläinen, 2010;Lu & Fletscher, 2009;National Research Council, 2012;Papert, 1996;Park & Jeon, 2015;Wilensky & Reisman, 2006;Williamson, 2016;Wing, 2006) 1.4. Data organization 1 0 9 8 18 (Barr, Harrison & Conery, 2011;Berland & Wilensky, 2015;Bers, 2010;Guzdial, 2008;Kafai & Burke, 2014;Kilpeläinen, 2010;Papert, 1996;National Research Council, 2010;Sengupta et al, 2013;…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Barr, Harrison & Conery, 2011;Basawapatna et al, 2011;Berland & Wilensky, 2015;Bers, 2010;ISTE & CSTA, 2011;Denning, 2012;Furber, 2012;Guzdial, 2008;Kafai, 2016;Kilpeläinen, 2010;Lu & Fletscher, 2009;NAACE, 2014;Papert, 1996;Snapp & Neumann, 2015;Williamson, 2015;Williamson, 2016) ies. Basawapatna et al, 2011;Berland & Wilensky, 2015;Bers, 2010;ISTE & CSTA, 2011;Furber, 2012;Grover & Pea, 2013;Guzdial, 2008;Kilpeläinen, 2010;Lu & Fletscher, 2009;National Research Council, 2012;Papert, 1996;Park & Jeon, 2015;Wilensky & Reisman, 2006;Williamson, 2016;Wing, 2006) 1.4. Data organization 1 0 9 8 18 (Barr, Harrison & Conery, 2011;Berland & Wilensky, 2015;Bers, 2010;Guzdial, 2008;Kafai & Burke, 2014;Kilpeläinen, 2010;Papert, 1996;National Research Council, 2010;Sengupta et al, 2013;…”
Section: Resultsmentioning
confidence: 99%
“…Data organization 1 0 9 8 18 (Barr, Harrison & Conery, 2011;Berland & Wilensky, 2015;Bers, 2010;Guzdial, 2008;Kafai & Burke, 2014;Kilpeläinen, 2010;Papert, 1996;National Research Council, 2010;Sengupta et al, 2013;Williamson, 2016) 1.5. Basawapatna et al, 2011;Berland & Wilensky, 2015;Guzdial, 2008;Williamson, 2016) (Barr & Stephenson, 2011;Bundy, 2007;Denning & Freeman, 2009;Denning, 2012;Grover & Pea, 2013;Guzdial, 2008;Jacobson & Wilensky, 2006;Lu & Fletscher, 2009;Miller & Settle, 2011;National Research Council, 2012;Papert, 1996;Snapp & Neumann, 2015;Williamson, 2016;Wing, 2006;Wolz et al, 2011;Yadav et al, 2014) 2.2. Programming processes 0 0 9 4 13 (Aho, 2012;Basawapatna et al, 2011;Denning, 2012;Kafai, 2016;Lu & Fletscher, 2009;Wing, 2008) ies As observed in Table 2, CT was defined mostly within the context of problem solving, technology and thinking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mishra and Yadav (2013) have argued that computational thinking goes beyond typical human-computer interactions within the school curriculum; instead, they argued that human creativity could be augmented by computational thinking, in particular with the use of automation and algorithmic thinking (Van Dyne & Braun, 2014). However, researchers argue despite the best efforts to articulate that computational thinking is more than just "programming", the misconception that the two are the same remains (Lu & Fletcher, 2009;Qualls & Sherrell, 2010).…”
Section: Computational Thinking: Literature Reviewmentioning
confidence: 99%
“…Recently, an interesting study by Selby (2013) Wing and several other authors call for incorporating computational thinking into formative education of children (Wing 2008), (Lu and Fletcher, 2009), (Lee et al, 2011) and (Hu, 2011). In some countries the focus is still on implementing informatics education only into secondary school, see e.g.…”
Section: Programming As a Component Of School Informaticsmentioning
confidence: 99%